MODEL BUILDING OF THE SYSTEM OF INFORMATION PROTECTION AND CONTROL ROBOTS SUPPLY COMPLEXES OF THE RAILWAYS - Matusievich, O. O. (Science and Transport Progress, 2007)
A model of protecting the information of telecontrol complexes for operating railway power supply devices has been offered and a rational option of creating the system of information protection has been selected.